KEPEMIMPINAN INSTRUKSIONAL DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU - Najmul Hidayat, Ayi; Khoiriyah, Nikmatul; Saofanita, Saofanita; Sukmawati Kusnadi, Fitria (Penerbit Lafadz Jaya, 2025)
The instructional leadership of the principal plays a crucial role in guiding and directing teachers to improve their professional competence in line with the demands of educational development. However, in practice, there are still teachers who have not fully demonstrated optimal abilities in designing and implementing effective learning. The purpose of this study is to analyze how the principal’s instructional leadership functions as both a role model and a trainer. This study employed a qualitative approach using the case study method. Interviews with the principal revealed that various activities have been implemented as part of instructional leadership practices, such as learning supervision, internal training (In-House Training), lesson study, and the dissemination of best practices through learning communities. The principal also actively involves teachers in planning these programs through discussion forums. This involvement strengthens the relevance of the programs to the actual needs of teachers, as they are based on reflections from the previous year’s teacher performance assessments. Based on the findings, it can be concluded that the principal’s instructional leadership at SMP Negeri 1 Bojongsoang has had a positive impact on improving teachers’ professional competence.